2023
DOI: 10.1002/ptr.7808
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine suppresses colorectal cancer progression by inhibiting NLRP3 inflammasome activation through mitophagy induction in vitro and in vivo

Abstract: Chinese herb Radix sophorae tonkinensis extract oxymatrine shows anticancer effects.This study evaluated the role of oxymatrine in colorectal cancer (CRC) and the underlying molecular events in vitro and in vivo. CRC cells were treated with different doses of oxymatrine to assess cell viability, reactive oxygen species production, gene expression, and gene alterations. Meanwhile, mouse xenograft and liver metastasis models were used to assess the effects of oxymatrine using histology examination, transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…OMT is an alkaloid mainly extracted from Sophorae Flavescentis Radix [ 96 ]. OMT effectively increased muribaculaceae, bifidobacterium abundance, lachnospiraceae, and ruminococcaceae, inhibited staphylococcaceae and bacteroides growth and regulated the intestinal flora structure in DSS-induced colitis [ 97 ].…”
Section: Tcm Ingredients For the Uc Treatmentmentioning
confidence: 99%
“…OMT is an alkaloid mainly extracted from Sophorae Flavescentis Radix [ 96 ]. OMT effectively increased muribaculaceae, bifidobacterium abundance, lachnospiraceae, and ruminococcaceae, inhibited staphylococcaceae and bacteroides growth and regulated the intestinal flora structure in DSS-induced colitis [ 97 ].…”
Section: Tcm Ingredients For the Uc Treatmentmentioning
confidence: 99%
“…OMT, an established bioactive monomer (Bi et al, 2012, Liang et al, 2023, was sourced from Shanghai Yuan-ye Biotechnology Co., Ltd., with its chemical structure illustrated in (Fig. 1A).…”
Section: Omt Characterization and Cytotoxicity Assessmentmentioning
confidence: 99%
“…Traditional Chinese Medicine (TCMs) holds promise in antiviral strategy development due to its mild nature and low likelihood of inducing drug resistance. Oxymatrine (OMT), an active monomer extracted from various TCMs including Sophora avescens Ait and Radix Sophorae Tonkinensis (Bi et al, 2012, Liang et al, 2023, has demonstrated e cacy in managing chronic hepatitis B (Lu et al, 2004). Besides its hepatoprotective role, OMT exhibits potential against tumorigenesis, in ammation, and bacterial infections (Li et al, 2022, Cao et al, 2023, Zhang et al, 2023a.…”
Section: Introductionmentioning
confidence: 99%
“…OMT [16,17] was procured from Shanghai Yuan-ye Biotechnology Co., Ltd. (Shanghai, China) The chemical structure of OMT is delineated in Figure 1A. To assess cytotoxicity, PMVECs were initially seeded in a 96-well polypropylene plate at a density of 10,000 cells per mL, using 100 µL of medium per well, and incubated at 37 • C in an atmosphere containing 5% CO 2 .…”
Section: Omt Characterization and Cytotoxicity Assessmentmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) offers a distinct perspective on antiviral therapy, emphasizing treatments that are less likely to induce drug resistance. Oxymatrine (OMT), a quinolizidine alkaloid extracted from the roots of Sophora flavescens Aiton and Sophora tonkinensis Gagnep (Fabaceae) [16,17], exhibits a broad spectrum of biological activities [18], including hepatoprotection, anti-tumorigenesis, anti-inflammation, and antibacterial effects [19][20][21]. Its capacity to modulate the immune response and inhibit viral replication of hepatitis B virus (HBV) in transgenic mice underscores its potential as an immunomodulatory agent [22].…”
Section: Introductionmentioning
confidence: 99%